PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN DAN PENGAWASAN TERHADAP KUALITAS LAPORAN KEUANGAN - Yusni, Yusni; Apriana, Ririn; Ndiak, Rosma (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
The purpose of this study is to determine the effect of the Implementation of Government Accounting Standards and Financial Supervision on the Quality of Financial Reports at the Banggai Regency Human Resources Development Agency Office. The analysis method used in this study is a quantitative analysis method, the analysis tool used to analyze data using SPSS 25. While the data sources in this study use primary data and secondary data. Based on the results of data analysis using SPSS 25, it shows that the results of the t-test show that all independent variables, namely the Implementation of Government Accounting Standards (X1), and Financial Supervision (X2), have a partial influence on the Quality of Financial Reports (Y) at the Banggai Regency Human Resource Development Agency Office. From the results of the ANOVA (analysis of variance) test or F test, the F-count is 8.781 and the F-table is 3.29. With this comparison, it can be seen that the F-count = 8.781> F-table value = 3.29, which means that it simultaneously has a positive and significant effect, and from the results of the study, it is partially shown that the variable for the application of government accounting standards (X1) has a regression coefficient value of 0.478 and the t-test value shows a t-count value = 2.514> from the t-table value = 2.034. This shows that the variable for the application of government accounting standards (X1) has an effect on the quality of financial reports (Y) and the financial supervision variable (X2) has a regression coefficient value of 0.411 and a value of The t-test shows the t-count value = 2.881 > from the t-table value = 2.034, this shows that partially the financial supervision variable has a positive and significant influence on the quality of financial reports (Y) at the Banggai Regency Human Resources Development and Personnel Agency,